A Gene Expression Atlas of the Domestic Water Buffalo (Bubalus bubalis) - Young, Rachel; Lefevre, Lucas; Bush, Stephen J.; Joshi, Akshay; Singh, Salam Herojeet; Jadhav, Santosh Kumar; Dhanikachalam, Velu; Lisowski, Zofia M.; Iamartino, Daniela; Summers, Kim M.; Williams, John L.; Archibald, Alan L.; et al. (Frontiers in Genetics, 2019)
The domestic water buffalo (Bubalus bubalis) makes a major contribution to the global agricultural economy in the form of milk, meat, hides and draught power. The global water buffalo population is predominantly found in Asia, and per head of population more people depend upon the buffalo than on any other livestock species. Despite its agricultural importance, there are comparatively fewer genomic and transcriptomic resources available for buffalo than for other livestock species. We have generated a large-scale gene expression atlas covering multiple tissue and cell types from all major organ systems collected from three breeds of riverine water buffalo (Mediterranean, Pandharpuri and Bhadawari), and used the network analysis tool Graphia Professional to identify clusters of genes with similar expression profiles. Alongside similar data we and others have generated for ruminants as part of the Functional Annotation of Animal Genomes Consortium, this comprehensive transcriptome supports functional annotation and comparative analysis of the water buffalo genome.